Penerapan Gel Aloe Vera Terhadap Penyembuhan Luka Ulkus Diabetikum Di Klinik Luka Rasika Gunungkidul - Muhammad Rafli Ramadhani; Exda Hanung Lidiana (Journal of Educational Innovation and Public Health, 2023)
Background of study: Diabetic ulcers is a complication of diabetes mellitus resulting from sensory, motor, autonomic neuropathy and/or vascular disorders of the limbs. One of the diabetic ulcer treatment techniques is using aloe vera gel. Aloe vera contains anti-bacterial, anti-inflammatory and can repair tissue damage of diabetic ulcers. Objective: to determine changes and developments after applying aloe vera gel to diabetic ulcer wound healing. Methods: This research uses descriptive case studies by observing nursing care for diabetic ulcer patients using aloe vera gel at the Rasika Gunungkidul Wound Clinic with an application 6x and application is carried out every 2 days using the Bates-Jensen Wound Assessment Tool. Results: The results of the assessment score before application in respondent 1 score 32 points with categories wound degeneration and respondent 2 score 21 points with categories wound degeneration. After application with aloe vera gel the score on respondent 1 was 21 points with categories wound degeneration while on respondent 2 was 10 points with categories wound regenration. The two respondents had a decrease in score which indicated that the wound had progressed significantly. Conclusion: The application of aloe vera gel can be used as an effective non-pharmacological method for diabetic ulcer wound.